Unwritten Rome - Wiseman, T. P. (Liverpool University Press, 2014)
Wiseman presents an imaginative and appealing picture of the early society of pre-literary Rome as a free and uninhibited world in which the arts and popular entertainments flourished. This original angle allows the voice of the Roman people to be retrieved empathetically from contemporary artefacts and figured monuments, and from selected passages of later literature